The Short-Term Efficacy of Straw Incorporation on Soil Detachment in Sloping Farmland - Chong Yao; Songzhu Ye; Siyuan Chen; Zhijia Gu; Wei Yan; Ming Zhu; Li Song; Mingjun Zhang; Faqi Wu (Agriculture)
Straw incorporation is applied in sloping farmland to coordinate soil water, fertilizer, air, heat, and soil erosion control in soil loss areas. Straw incorporation is considered to significantly affect soil detachment. However, the knowledge about the influence of soil consolidation by rainfall and mechanical effect by straw incorporation in short-term on soil detachment capacity (Dc) by rill flow is still limited. The current study was carried out to quantify the impact of soil consolidation by rainfall and mechanical effect under straw incorporation on Dc. The soil samples were collected from seven different plots (straw incorporation rates of 0 (CK), 0.2, 0.4, 0.6, 0.8, and 1.2 kg m−2 with rainfall simulation of 30 mm and without straw incorporation and rainfall simulation (CK0)) and subjected to flume scoring experiments. The results indicated that the Dc with different straw incorporation rates significantly differed and decreased by 39.16–60.04%, compared with CK. The Dc exhibited a power function relationship with hydraulic parameters and stream power was the most appropriate hydraulic variable to express Dc for different straw incorporation rates. The hydraulic characteristics, straw incorporation rates, and interaction between them have a significant impact on the Dc, and Dc was more sensitive to hydraulic characteristics. The contribution rates to Dc reduction benefits by soil consolidation exceeded those by mechanical effect of incorporated straw. The impact of incorporated straw with rainfall simulation in short-term on Dc has a threshold of a straw incorporation rate of 0.4 kg m−2. The Dc for different straw incorporation rates could be satisfactorily simulated using the composite equation of binary power-exponential function of stream power and soil cohesion. This research reveals the impacts of soil consolidation by rainfall and the mechanical effect of incorporated straw on Dc, and offers a framework for predicting and managing soil erosion in areas susceptible to soil loss.